Abnormal Platelet Serotonin Uptake and Binding Sites in Myeloproliferative Disorders - Caranobe, C; Sié, P; Fernandez, F; Pris, J; Moatti, S; Boneu, B (Thrombosis and Haemostasis, 1984)
A simultaneous investigation of the kinetics of serotonin (5 HT) uptake and of binding sites was carried out in the platelets of normal subjects and of 10 patients affected with various types of myeloproliferative disorders (MD). The 5 HT uptake was analysed according to the Lineweaver-Burk and the Eadie-Hofstee methods. With the two methods, the patient’s platelets exhibited a dramatic reduction of the Vi max and of the Km; in some patients the Eadie-Hofstee analysis revealed that a passive diffusion phenomenon is superimposed on the active 5 HT uptake at least for the higher concentration used. The binding data were analysed with the Scatchard method. Two classes of binding sites (high affinity - low capacity, low affinity - high capacity) were found in normal subjects and patients. Pharmacological studies with imipramine, a specific inhibitor of 5 HT uptake, suggested that both the sites are involved in 5 HT uptake. The number of both binding sites was significantly decreased in patient’s platelets while the affinity constants of these binding sites were not significantly reduced in comparison with those of the control subjects. No correlations were found between Vi max, Km and the number of binding sites. These results suggest that a reduction in the number of platelet membrane acceptors for 5 HT commonly occurs in myeloproliferative disorders but does not provide a full explanation of the uptake defect.
Keywords: Myeloproliferative disorders; Platelet serotonin uptake; Platelet serotonin binding sites